Analysis of the Influence of Learning Organization, Work Motivation, and Work Environment on Employee Performance Mediated by Job Satisfaction Among Employees at PT. XYZ Tolitoli - I Made Agus Adi Mertha; Juanna Judith Huliselan (International Journal of Economics Accounting and Management, 2025)
In the era of Volatility, Uncertainty, Complexity, and Ambiguity (VUCA), companies are required to maximize and professionalize human resource management to achieve optimal performance in reaching organizational goals. This study aims to analyze the influence of Learning Organization, Work Motivation, and Work Environment on Employee Performance with Job Satisfaction as a mediating variable. The research uses a quantitative approach with a cross-sectional method. Data were collected through an online questionnaire modified from previous research instruments. The respondents consisted of 75 employees at PT. XYZ located in Tolitoli with a minimum work tenure of one year. Data analysis was conducted using SmartPLS software. The results show that all variables have a positive and significant influence on Job Satisfaction and Employee Performance, and Job Satisfaction can mediate the influence of Learning Organization, Work Motivation, and Work Environment on Employee Performance. These findings provide theoretical implications for human resource management and managerial implications for PT. XYZ Tolitoli in formulating strategies to improve employee performance. The study also acknowledges limitations, particularly in scope and methods used, and recommends further research with broader coverage and approaches